Development and testing of a model of interactive innovation adoption in health care. Issue 1 (24th October 2017) - Pollock, Danielle
ABSTRACT: Understanding the factors that lead groups of professionals in healthcare organizations to adopt or reject new innovations for communication and information sharing is vital for those seeking to support the information needs of these communities. This poster presents a new model for the study of the diverse factors that impact interactive innovation adoption in research‐intensive healthcare environments. It further details a method for testing the model by examining the adoption of two different interactive innovations by physicians in training at an academic medical center, one innovation developed for virtual communication between providers and the other developed to improve face‐to‐face communication in the physical world. Preliminary results from the first phase of the study, including barriers to adoption identified by the study participants, will be also displayed.